Ritual Communication in the Fulfillment of Promises (Nazars) at the Tomb of Puyang Serunting (Study in Pelangkenidai Village) - Shefa Gustaza Putri; Kun Budianto; Muslimin Ritonga (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study examines ritual communication in the fulfillment of promises (vows) at the tomb of Puyang Serunting, Pelangkenidai Village, with a focus on: the process of implementing ritual communication and the form of ritual communication that appears during the fulfillment of vows. The research uses a qualitative ethnographic approach; Data was collected through participatory observation, in-depth interviews with key informants (traditional leaders, grave holders, and pilgrims), and field documentation. The results of the study showed that the process of implementing ritual communication included the preparation stage (intention and formulation of promises), ritual implementation (prayer reading, joint procession, and other symbolic actions), and socio-religious follow-up (reporting of promise fulfillment and community recognition). The process is colored by the negotiation of roles between ritual actors, customary norms, and local religious interpretations that determine the sequence of actions and the legitimacy of the ritual. The forms of ritual communication found included verbal communication (pronunciation of vows, prayers, and narratives of gratitude), nonverbal communication (body gestures, ritual clothing, and physical procedures at the tomb), and collective communication (procession rituals, joint prayer readings, and social affirmation ceremonies). This communication serves to represent individual intentions, build common meaning, and reproduce the social structure and religious values in Pelangkenidai Village. These findings enrich the understanding of local ritual dynamics and provide a basis for recommendations for the preservation of cultural practices.